Evaluación del sistema de seguridad y salud ocupacional en la empresa Orpinco limitada de la ciudad de Manta - Macías Bravo, Cristian Eduardo (2025)
The present study was developed under the objective of evaluating the occupational health and safety system for the prevention of occupational risks in the workers of Orpinco Ltda. In order to achieve this study objective, evaluation methodologies such as the observation sheet and instruments such as the interview and the structured survey were used according to the criteria for the evaluation of occupational risks of the Ministry of Labor. The results showed inconsistencies in the management of ergonomic and psychosocial risks by the company's management, as well as deficiencies in the dimensions of management in occupational risk prevention, the structure of prevention against falling objects and people, physical risks, occupational health management, and the dimension of permanent services. The inconsistencies detected could trigger factors that will affect the health and welfare of workers, unproductiveness and economic repercussions to the company, so it is necessary to adopt the improvement plan proposed in this research for their respective improvements.